Depression and Anxiety in Voluntarily Unemployed People: A Systematic Review - Borrelli, Ivan; Santoro, Paolo Emilio; Melcore, Giuseppe; Perrotta, Antongiulio; Rossi, Maria Francesca; Gualano, Maria Rosaria; Moscato, Umberto (La Medicina del Lavoro, 2024)
Background: Unemployment impacts people’s physical and psychological well-being, and gender and age affect mental health among the unemployed. Despite the correlation between unemployment and negative mental health outcomes being largely investigated in scientific literature, research on voluntarily unemployed individuals is scarce. A systematic review was performed on studies evaluating mental health outcomes in voluntarily unemployed adults. Methods: Following the PRISMA statements, three databases were screened; research articles written in English investigating the relationship between mental health outcomes and employment status were included. The quality of articles was assessed using the Newcastle-Ottawa Scale. Results: The initial search yielded 727 records; 4 studies were included in this systematic review. One study reported voluntarily unemployed people as less depressed than employed and unemployed people, one as more depressed than employed but less than unemployed people, one reported voluntarily unemployed people as less anxious but more depressed than employed and less anxious and depressed than unemployed people, one study reported voluntarily unemployed men as depressed and anxious more often than employed men. Further research should investigate mental health outcomes in voluntarily unemployed people and strategies to bring back these individuals into the workforce.